Bi-doped La1.5Sr0.5Ni0.5Mn0.5O4+δ as an efficient air electrode material for SOEC. (22nd October 2021) - Jiang, Huaguo; Lu, Zeming; Qian, Bin; Wang, Shun; Yin, Bo; Zheng, Yifeng; Ge, Lin; Chen, Han; Zhang, Caizhi
Abstract: Bi-doped La1.5-x Bix Sr0.5 Ni0.5 Mn0.5 O4+δ (LBSNM-x, x = 0, 0.05, 0.1, 0.15) was investigated as a potential air electrode for solid oxide electrolysis cell (SOEC). The effect of Bi doping on the structure, electrical conductivity, chemical compatibility with GDC electrolyte, electrochemical performance and thermal expansion coefficients (TECs) were investigated. XRD characterization results show that the solid solution content of Bi is less than or equal to 0.1. XPS characterization results indicate that Bi doping increases the oxygen vacancy content of LBSNM-x air electrode and thus greatly benefits its oxygen evolution reaction. Among the Bi-doped samples, LBSNM-0.1 electrode has the best electrochemical performance with its lowest Rp (polarization resistance) of 0.28 Ω cm 2 at 800 °C based on LBSNM-0.1/GDC half-cell. LBSNM-0.1 single cell with 70%CO2 + 30%CO fuel gas feed on the fuel electrode has achieved current density of 811 mA cm −2 at 800 °C and 1.4 V, a 62.2% increase relative to that of LSNM single cell. In addition, LBSNM-0.1 single cell exhibits excellent stability at 800 °C and 1.3 V with 70%CO2 + 30%CO feed gas on the fuel electrode. These results prove that Bi-doped LBSNM-0.1 is an efficient air electrode for SOEC. Highlights: Bi-doped LSNM is studied as potential air electrode for direct electrolysis of CO2. The introduction of Bi can greatly decrease the Rp of LSNM. The LBSNM-0.1 single cell shows a current density increased by 62.2% compared with that of LSNM at 1.4 V and 800 °C. LBSNM-0.1 air electrode has an impressive stability in CO2 electrolysis mode.